Investigation the microbial community and quality of Suanjiang tofu with the addition of wheat flour - Shan Yu; Jiangli Wu; Fuyi Hui; Jin Fan; Wei Zhang; Zhengbin Yang; Ziru Dai; Xuefeng Zeng (npj Science of Food)
Abstract In this study, wheat flour at different contents was mixed with soy whey and fermented to produce high-quality Suanjiang tofu. The objective was to evaluate the impact of wheat flour supplementation on the physicochemical, structure, and qualitative properties of Suanjiang tofu, and explore the correlation between wheat flour content and bacterial population. The results demonstrated that wheat flour supplementation not only increased tofu yield but also enhanced the formation of a dense and uniform three-dimensional protein network, reduced protein aggregate size, and significantly improved hardness (p < 0.05). Additionally, the hydrophobic interactions and disulfide bonds playing a more critical role than ionic and hydrogen bonds in stabilizing the gel network. Moreover, higher wheat flour concentrations reduced bacterial diversity, with Acetobacter rapidly proliferating and becoming the dominant genus (97% relative abundance). These findings provide valuable insights into the between wheat flour and soy whey and practical guidance for specialty tofu production.